1999
DOI: 10.1037/0022-0663.91.1.146
|View full text |Cite
|
Sign up to set email alerts
|

Authoritative parenting and college students' academic adjustment and success.

Abstract: This study examined connections between college students' adjustment and success and characteristics of their relationships with their parents. A sample of 236 students completed the Student Attitudes and Perceptions Survey, a 135-item anonymous self-report instrument. Students' grades, confidence level, persistence, task involvement, and rapport with their teachers were generally predicted by both current and childhood levels of parental autonomy granting, demandingness, and supportiveness. Ratings of parenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
71
0
7

Year Published

2001
2001
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(92 citation statements)
references
References 48 publications
(40 reference statements)
10
71
0
7
Order By: Relevance
“…Furthermore, the stability of parental influence on academic development has also been exam ined. A cross sectional study, conducted by Strage and Brandt (1999), found a stronger correlation between the support, demands, and autonomy of parents and positive academic orientation of first year college students, compared to seniors. In a later study, Ratelle, Larose, Guay, and Senécal (2005) concluded that success in a college science program was attributed to feelings of support and competence from parents.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the stability of parental influence on academic development has also been exam ined. A cross sectional study, conducted by Strage and Brandt (1999), found a stronger correlation between the support, demands, and autonomy of parents and positive academic orientation of first year college students, compared to seniors. In a later study, Ratelle, Larose, Guay, and Senécal (2005) concluded that success in a college science program was attributed to feelings of support and competence from parents.…”
Section: Resultsmentioning
confidence: 99%
“…Within the current study, parental involvement was operationally defined as perceived expectations for school performance, direct reinforcement of improved academic performance, general academic guidance and support, encouragement of communication with teachers, and parental participation with school activities (Keith, Reimers, Fehrmann, Pottebaum, & Aubey, 1986;Fan & Chen, 2001). Academic mastery was operationally defined as students' confidence in their ability to complete college, degree to which students persist in the face of difficulty or failure, students' ability to avoid distractions and maintain focus, degree to which students perceive teachers as resources not threats, intellectual curiosity, and overall GPA (Strage & Brandt, 1999). We hypothesized that for the current sample, a positive correlation would be found between parental involvement in high school and academic mastery in college, specifically at the first and second year level.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has shown inconclusive results with traditional student populations. Some studies found a positive association between family dynamics and college adjustment (Armsden & Greenberg, 1987;Bradford & Lyddon, 1993;Feenstra et al, 2001;Haemmerlie et al, 1994;Kalsner & Pistole, 2003;Kemp & Neimeyer, 1999;Kenny & Donaldson, 1991Kenny & Perez, 1996;Lapsley & Edgerton, 2002;Mallinckrodt, 1992;McCarthy et al, 2001;Protinsky & Gilkey, 1996;Rice et al, 1995;Rice & Whaley, 1994;Strage, 1998;Strage & Brandt, 1999), while others showed no relationship or a negative one (Berman & Sperling, 1991;Fass & Tubman, 2002;Lopez et al, 1986;Palladino-Schultheiss & Blustein, 1994b;Rice et al, 1990). The current study focused on college adjustment factors as the outcome variable in an attempt to provide further clarification about the relationship between family relationship dynamics and college adjustment.…”
Section: Hypotheses Of Studymentioning
confidence: 99%
“…College adjustment has been found to be associated with family relationship dynamics (Armsden & Greenberg, 1987;Bradford & Lyddon, 1993;Feenstra et al, 2001 ;Haemmerlie et al, 1994;Kalsner & Pistole, 2003;Kemp & Neimeyer, 1999;Kenny & Donaldson, 1991Kenny & Perez, 1996;Lapsley & Edgerton, 2002;Lapsley et al, 1989;Mallinckrodt, 1992;Protinsky & Gilkey, 1996;Rice et al, 1995;Rice & Whaley, 1994;Strage, 1998;Strage & Brandt, 1999;Wintre & Sugar, 2000) and psychological coping (Brooks & DuBois, 1995;Feenstra et al, 2001;Kerr, 1995;Larose et al, 1998;Stevens & Walker, 1996;Wintre & Yaffe, 2000;Zea et al, 1995). In addition, studies have shown that family relationship dynamics impact the adjustment of college students even with prior academic achievement controlled (Brooks & DuBois, 1995;Cutrona et al, 1994) and another found family dynamics to be associated with adaptation to college even after factoring out individual student coping (Feenstra et al, 2001).…”
Section: Hypotheses Of Studymentioning
confidence: 99%
See 1 more Smart Citation